Ultrastructural changes of cell morphology and viral morphogenesis of two ecotypes of dengue virus infection in human monocytic U-937 cell - Fish-Low, Cheng Yee; AbuBakar, Sazaly; Othman, Fauziah; Chee, Hui Yee (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Dengue virus (DENV) is maintained and circulated in both sylvatic/enzootic and endemic/human cycles and spill over infection of sylvatic DENV into human populations has been reported. Extensive deforestation and increase human activities in forest may increase the risk of human exposure to sylvatic dengue infection and this may become a threat to human. Present study investigated the changes in cell morphology and viral morphogenesis upon infection with sylvatic and endemic ecotypes in human monocytic U-937 cells using transmission electron microscopy. Autophagy, a process that is either pro-viral or anti-viral, was observed in U-937 cells of both infections, however only the replication of endemic DENV was evidenced. An insight into the infection responses of sylvatic progenitors of DENV in susceptible host cells may provide better understanding on dengue emergence in human populations.